Andrographolide Inhibits Mechanical and Thermal Hyperalgesia in a Rat Model of HIV-Induced Neuropathic Pain - Yi, Zhihua; Ouyang, Shuai; Zhou, Congfa; Xie, Lihui; Fang, Zhi; Yuan, Huilong; Yang, Jinpu; Zou, Lifang; Jia, Tianyu; Zhao, Shanhong; Li, Lin; Shi, Liran; et al. (Frontiers in Pharmacology, 2018)
Aim: In this study, we investigated whether andrographolide can alleviate neuropathic pain induced by HIV gp120 plus ddC treatment and the mechanism of its action. Methods: The paw withdrawal threshold and the paw withdrawal latency were observed to assess pain behaviors in all groups of the rats, including control group, control combined with andrographolide treatment group, sham group, gp120 combined with ddC treatment group, gp120 plus ddC combined with A438079 treatment group, and gp120 plus ddC combined with andrographolide treatment by intrathecally injecting at a dose of 25 μg/20 μl group. The protein expression levels of the P2X7 receptor, tumor necrosis factor-α-receptor (TNFα-R), interleukin-1β (IL-1β), interleukin-10 (IL-10), phospho-extracellular regulated protein kinases (ERK) (pERK) in the L4-L6 dorsal root ganglia (DRG) were measured by Western blotting. Real-time quantitative polymerase chain reaction (RT-qPCR) was used to test the mRNA expression level of the P2X7 receptor. Double-labeling immunofluorescence was used to identify the co-localization of the P2X7 receptor with glial fibrillary acidic protein (GFAP) in DRG. Molecular docking was performed to identify whether the andrographolide interacted perfectly with the rat P2X7 (r P2X7) receptor. Results: Andrographolide attenuated the mechanical and thermal hyperalgesia in gp120 + ddC-treated rats and down-regulated the P2X7 receptor mRNA and protein expression in the L4-L6 DRGs of gp120+ddC-treated rats. Additionally, andrographolide simultaneously decreased the expression of TNFα-R and IL-1β protein, increased the expression of IL-10 protein in L4-L6 DRGs, and inhibited the activation of ERK signaling pathways. Moreover, andrographolide decreased the co-expression of GFAP and the P2X7 receptor in the SGCs of L4-L6 DRG on 14th day after surgery. Conclusion: Andrographolide decreased the hyperalgesia induced by gp120 plus ddC.